2022
DOI: 10.1038/s41467-022-33587-0
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility of functional neuronal assemblies supports human memory

Abstract: Episodic memories, or consciously accessible memories of unique events, represent a key aspect of human cognition. Evidence from rodent models suggests that the neural representation of these complex memories requires cooperative firing of groups of neurons on short time scales, organized by gamma oscillations. These co-firing groups, termed “neuronal assemblies,” represent a fundamental neurophysiological unit supporting memory. Using microelectrode data from neurosurgical patients, we identify neuronal assem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Neural coding is unlikely to be fully explained by pairwise interactions alone. Recent work in humans 27 suggested that groups of neurons that have significant co-firing tendencies can be categorized into cell assemblies whose expression is linked to episodic memory performance. We next evaluated whether integrated neural assemblies were detectable in our data and whether co-rippling across multiple electrodes facilitates their expression.…”
Section: Co-rippling Modulates the Expression Of Neuronal Assemblies ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Neural coding is unlikely to be fully explained by pairwise interactions alone. Recent work in humans 27 suggested that groups of neurons that have significant co-firing tendencies can be categorized into cell assemblies whose expression is linked to episodic memory performance. We next evaluated whether integrated neural assemblies were detectable in our data and whether co-rippling across multiple electrodes facilitates their expression.…”
Section: Co-rippling Modulates the Expression Of Neuronal Assemblies ...mentioning
confidence: 99%
“…We next evaluated whether integrated neural assemblies were detectable in our data and whether co-rippling across multiple electrodes facilitates their expression. We detected cell assemblies during NREM and waking according to previously described methods 27,28 . We divided neural spike trains from NREM and waking into 100 ms bins (roughly the duration of a ripple event) and normalized the binned firing rates for each neuron across the recording session.…”
Section: Co-rippling Modulates the Expression Of Neuronal Assemblies ...mentioning
confidence: 99%
“…For example, neurons that share common input [46] or targets [47] are more likely to form recurrent connections amongst themselves. Additionally, there is strong evidence that groups of highly interconnected neurons (neuronal assemblies) share common functions within recurrent networks [31, 48, 49]. Moreover, evidence has accumulated [50, 51] that different neurons type (excitatory and inhibitory subtypes) follow distinct spatial connectivity patterns, which have implications for neural computation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations found drift in the lateral temporal context contributed to successful recall of related items ( El-Kalliny et al, 2019 ). Gamma oscillations also coordinate contextually relevant neuronal assemblies ( Umbach et al, 2022 ). Our results build on this finding by characterizing drift in gamma oscillations and further describing how gamma activity is associated with context.…”
Section: Discussionmentioning
confidence: 99%